Highly efficient and reusable CuAu nanoparticles supported on crosslinked chitosan hydrogels as a plasmonic catalyst for nitroarene reduction - Ramírez, Oscar; Bonardd, Sebastián; Saldías, César; Leiva, Angel; Díaz Díaz, David (Environmental research, 2024)
The synthesis of CuAu-based monometallic (MNPs) and bimetallic nanoparticles (BNPs) supported on chitosan-based hydrogels for their application as catalysts is presented. The hydrogels consisted of chitosan chains cross-linked with tripolyphosphate (TPP) in the form of beads with an approximate average diameter of 1.81 mm. The MNPs and BNPs were obtained by the adsorption of metallic ions and their subsequent reduction with hydrazine, achieving a metallic loading of 0.297 mmol per gram of dry sample, with average nanoparticle sizes that were found between 2.6 and 4.4 nm. Both processes, metal adsorption and the stabilization of the nanoparticles, are mainly attributed to the participation of chitosan hydroxyl, amine and amide functional groups. The materials revealed important absorption bands in the visible region of the light spectra, specifically between 520 and 590 nm, mainly attributed to LSPR given the nature of the MNPs and BNPs inside the hydrogels. Subsequently, the hydrogels were evaluated as catalysts against the reduction of 4-nitrophenol (4NP) into 4-aminophenol (4AP), followed by UV–visible spectroscopy. The kinetic advance of the reaction revealed important improvements in the catalytic activity of the materials by synergistic effect of BNPs and plasmonic enhancement under visible light irradiation, given the combination of metals and the light harvesting properties of the nanocomposites. Finally, the catalytic performance of hydrogels containing BNPs CuAu 3:1 showed an important selectivity, recyclability and reusability performance, due to the relevant interaction of the BNPs with the chitosan matrix, highlighting the potential of this nanocomposite as an effective catalyst, with a potential environmental application. [Display omitted] •CuAu BNPs synthesized on biobased hydrogels were used in nitrophenol reduction.•Cu and Au present a bimetallic synergy for catalysis in nanostructured materials.•Using visible light radiation improves the reaction kinetics by LSPR activation.•Chitosan enables an easy and effective reusability of the catalyst in several runs.